Gauging the Importance of Strategic Foresight Factors Affecting Public Organisational Dynamic Capabilities - Bakheeta Saeed Ali Almansoori, Siti Azirah Asmai (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a study on determine the importance of strategic foresight factors affecting dynamic capabilities of an organisation. Literature review found that 19 factors which are clustered in five domains of strategic foresight namely environmental scanning; scenario planning; knowledge creation; culture and formal organization. Data collection adopted a purposive random sampling technique of questionnaire survey amongst individuals who involved in decision-maker position of UAE organizations. A total of 209 respondents participated in the survey. The analysis of the collected data found that 11 of the factors are having high degree of importance and for the domains, four out of five domains are having high degree of importance. It also found that domain culture is having the highest rank amongst the five domains then follows by domain scenario planning, formal organisation, knowledge creation and the last rank is the environmental scanning domain. This research can conclude that the utilisation of strategic foresight has a potential role in improving public organisations as well as the country’s national economic expansion. Therefore, policy makers and decision makers need to be innovative and focus on combining strategic foresight and dynamic capabilities through utilizing the significant/important factors that enhance the current status of organizations with future nature and requirements of work.